Expression profiles of the Tau-associated genes GSk3β, CAPN1, and CDK5R1 in the brain cortex of aged female cynomolgus monkeys with cognitive impairment - Huda S. Darusman; Lis Rosmanah; Sela S. Mariya; Uus Saepuloh; Yuliana Yuliana; Jann Hau (Open Veterinary Journal)
Background: Alzheimer's disease (AD) is characterized by the buildup and aggregation of misfolded proteins in the brain, including amyloid-β (Aβ) and hyperphosphorylated tau. The hyperphosphorylation state of Tau protein plays an important role in the development of AD. Our previous studies developed and characterized the cynomolgus monkey as a spontaneous animal model of AD.